A Five-Dimensional Network Meta-Analysis of Chinese Herbal Injections for Treating Acute Tonsillitis Combined With Western Medicine - Huang, Peiying; Li, Yin; Huang, Bixuan; Zhao, Shuai; Chen, Li; Guan, Hansu; Chen, Yan; Feng, Yuchao; Huang, Xiaoyan; Deng, Yi; Lei, Sisi; Wu, Qihua; et al. (Frontiers in Pharmacology, 2022)
Background: Acute tonsillitis has high morbidity. Chinese herbal injections (CHIs) were reported to be useful in treating acute tonsillitis and might reduce the probability of antibiotic resistance. Nevertheless, the optimal strategy for combining CHIs with western medicine (WM) to treat acute tonsillitis remains unclear. Methods: We retrieved data from the following databases with retrieval time from inception to January 11, 2022: PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang Database, Weipu Journal Database, and Chinese Biomedical Literature Database. Version 2 of the Cochrane risk-of-bias tool (ROB2) was used for evaluating the quality of the included studies. R 4.1.2, STATA 14.0, and Python 3.10.4 were employed for network meta-analysis, with 5-dimensional K-means cluster analysis, meta-regression analyses, sensitivity analyses, and subgroup analyses. Results: A total of 110 randomized controlled trials including 12,152 patients were included. All the studies were rated as “high risk” and “some concerns”. In terms of improving clinical effectiveness rate, Qingkailing injection+WM ranked ahead of other interventions (89.51%). Regarding reducing antipyretic time, Reduning injection+WM had the highest-ranking probability (68.48%). As for shortening sore throat relief time, Shuanghuanglian injection+WM ranked first (76.82%). Concerning shortening red and swollen tonsils relief time, Yanhuning injection+WM possessed the highest-ranking probability (89.17%). In terms of reducing tonsillar exudate relief time, Xuebijing injection+WM ranked ahead of the other interventions (94.82%). Additionally, the results of the cluster analysis suggested that Xuebijing injection+WM, Reduning injection+WM, and Yanhuning injection+WM were probably the best interventions. Furthermore, adverse drug reactions rate of Xuebijing injection+WM, Reduning injection+WM, Yanhuning injection+WM, Qingkailing injection+WM, and Shuanghuanglian injection+WM were individually 0.00%, 3.11%, 3.08%, 4.29%, and 4.62%. Conclusions: CHIs+WM have a better impact on patients with acute tonsillitis than WM alone. Xuebijing injection, Reduning injection, and Yanhuning injection might have potential advantages in treating the disease. Concerning adverse drug reactions, Xuebijing injection is presumably the optimal CHI. More high-quality studies are needed to further confirm our findings.